Energy Regulation Mechanism and Therapeutic Potential of Asprosin - Hoffmann, Jennifer G. (Diabetes, 2020)
Genetic studies of patients with neonatal progeroid syndrome led to the discovery of the novel fasting-induced, glucogenic, and orexigenic hormone named asprosin, the C-terminal cleavage product of profibrillin. Upon secretion, asprosin travels to the liver, where it exerts a glucogenic effect through OR4M1, an olfactory G-protein–coupled receptor. It also crosses the blood-brain barrier to stimulate appetite-modulating neurons in the arcuate nucleus of the hypothalamus, exerting an orexigenic effect via an as yet unidentified receptor. Specifically, it stimulates appetite by activating orexigenic AgRP neurons and inhibiting anorexigenic POMC neurons. Studies have also focused on the therapeutic potential of inhibiting asprosin for treatment of obesity and type 2 diabetes, both of which are characterized by high levels of circulating asprosin. It has been shown that anti-asprosin monoclonal antibodies reduce blood glucose, appetite, and body weight, validating asprosin as a therapeutic target. Current work aims to uncover key features of the asprosin biology such as the identification of its neuronal receptor, identification of the secretion mechanism from adipose tissue, and development of anti-asprosin monoclonal antibodies as diabetes and obesity therapies.